Learning the State Language through Dubbed and Subtitled Movies: Attitudes of Kazakhstani Students - Kamzabek, Khadisha (Nazarbayev University Graduate School of Education, 2020)
According to the new Law on Cinematography, all foreign movies should now include obligatory Kazakh state language subtitles or dubbing in the public cinemas (Law on Cinematography, Article 9). Although the provision of the law is aimed at the promotion and protection of the state language, the translations are of poor quality, which provokes the resentment of the Kazakh-speaking population. Moreover, such promotion of the state language could be perceived as nationalistic and as an infringement by the Russian speaking population like in several other post-Soviet countries such as Estonia (Keedus, 2004), Ukraine (Pavlenko, 2008; Goodman, 2009; Polese, 2011), and Georgia (Sherouse, 2017). The purpose of this mixed methods study was to investigate the attitudes of Kazakhstani students towards learning the state language through Kazakh-language movies, identifying the similarities and/or differences in terms of the dominant language of students (Kazakh/Russian) and adaptation method provided in movies (dubbed/subtitled). The results based on questionnaire (134 participants) and interview (5 participants) answers indicate that Kazakhstani students are positive about learning the Kazakh language through movies. However, the attitudes were found to be more positive towards Kazakh dubbing than Kazakh subtitles, as the former may lead to language acquisition, and the latter is rather distracting and overloads the visual channel. The difference in the attitudes of Kazakh and Russian dominant students was that Kazakh-dominant students see Kazakh subtitles as an opportunity to understand Russian dubbing better. The findings of this research might contribute to the body of literature by filling in the gaps in previous audiovisual translation and language acquisition studies. The study may generate interest among scholars for further research in the field of multilingualism and help policymakers and educators reconsider the roles of movies and media in education.
Keywords: Dubbing; Kazakh-language movies; subtitles; Kazakhstani media; language in media; movie adaptation methods; the state language in media; students' attitudes; mixed methods research; Cognitive Theory of Multimedia Learning; bimodal subtitles; standard subtitles; reversed subtitles; audiovisual translation